A systematic review and meta-analysis on the association between PM2.5 exposure and increased influenza risk - Orr, Ava; Kendall, Rebekah L.; Jaffar, Zeina; Graham, Jon; Migliaccio, Christopher T.; Knudson, Jonathon; Noonan, Curtis; Landguth, Erin L. (Frontiers in Epidemiology, 2025)
IntroductionThis systematic review and meta-analysis investigate the relationship between PM2.5 exposure and increased influenza risk (e.g., increased hospital admissions, confirmed influenza cases), synthesizing previous findings related to pollutant effects and exposure durations.MethodsWe searched PubMed, Web of Science, and Scopus for relevant studies up to 1 January 2010, following Preferred Reporting Items for Systematic reviews and Meta-Analysis (PRISMA) guidelines for selection and analysis.ResultsOur review included 16 studies and found that a 10 μg/m3 increase in daily PM2.5 levels was associated with an increase of 1.5% rise in influenza risk (95% CI: 0.08%, 2.2%), with significant variations across different temperatures and lag times post-exposure. The analysis revealed heightened risks, with the most significant increases observed under extreme temperature conditions. Specifically, colder conditions were associated with a 14.2% increase in risk (RR = 14.2%, 95% CI: 3.5%, 24.9%), while warmer conditions showed the highest increase, with a 29.4% rise in risk (RR = 29.4%, 95% CI: 7.8%, 50.9%). Additionally, adults aged 18–64 were notably affected (RR = 4%, 95% CI: 2.9%, 5.1%).DiscussionThese results highlight PM2.5's potential to impair immune responses, increasing flu susceptibility. Despite clear evidence of PM2.5's impact on flu risk, gaps remain concerning exposure timing and climate effects. Future research should broaden to diverse regions and populations to deepen understanding and inform public health strategies.